Effects of Learner-Generated Outlining and Instructor-Provided Outlining on Learning from Text: A Meta-Analysis - Ponce-Arias, H (Elsevier Ltd, 2023)
Learning from printed text is a central academic task that may be challenging for students. Two ways to improve learning from text are to encourage learners to engage in generative learning strategies while reading, such as constructing an outline, or for instructors to include effective instructional design features, such as providing an outline with the text. A meta-analysis of studies comparing a group that was asked to generate an outline while reading a text to a control group that was not asked to outline found an average effect size of g+ = 0.59 on memory tests, g+ = 0.59 on comprehension tests, and g+ = 0.52 on writing assignments favoring learner-generated outlining. A meta-analysis of studies comparing a group that read a text containing an outline with a control group that read the same text without an outline found an effect size of g+ = 0.61 for memory tests and g+ = 0.34 for comprehension tests favoring instructor-provided outlining. Overall, there is encouraging evidence for the effectiveness of outlining as a generative learning strategy and for the effectiveness of outlining as an instructional design feature based on signaling, consistent with generative learning theory. © 2023 Elsevier Ltd